2011
DOI: 10.1111/j.1600-0846.2010.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

Is there any barrier impairment in sensitive skin?: a quantitative analysis of sensitive skin by mathematical modeling of transepidermal water loss desorption curves

Abstract: Whereas in the studies based in basal TEWL measurements only discrete differences were reported, the dynamic approach followed in this study provided unequivocal evidence of barrier impairment. The methodology enabled a more objective characterization of sensitive skin and can potentially be applied to the diagnosis/prediction of sensitivity; as well as the efficacy assessment of cosmetic products that are specifically designed to fulfill the needs of consumers with this skin condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 30 publications
2
69
0
4
Order By: Relevance
“…Most studies observed higher TEWL in the unchallenged skin of subjects with sensitive skin compared to those with nonsensitive skin [20,41,48,49] and in stingers compared to nonstingers [39,40,41,50,51], while only 2 studies identified significantly higher TEWL in sensitive skin [40,41]. Moreover, higher TEWL at baseline seems to correlate with a stronger TEWL increase following provocation [40]: plastic occlusion resulted in a significantly longer evaporation half-life time in subjects with sensitive skin [49], and a trend to increased recovery time of TEWL following SLS stimulation was also observed [20]. A stronger increase of TEWL was also found following SLS provocation both in sensitive versus nonsensitive atopic skin [52] and in a population of Japanese versus German women [53].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies observed higher TEWL in the unchallenged skin of subjects with sensitive skin compared to those with nonsensitive skin [20,41,48,49] and in stingers compared to nonstingers [39,40,41,50,51], while only 2 studies identified significantly higher TEWL in sensitive skin [40,41]. Moreover, higher TEWL at baseline seems to correlate with a stronger TEWL increase following provocation [40]: plastic occlusion resulted in a significantly longer evaporation half-life time in subjects with sensitive skin [49], and a trend to increased recovery time of TEWL following SLS stimulation was also observed [20]. A stronger increase of TEWL was also found following SLS provocation both in sensitive versus nonsensitive atopic skin [52] and in a population of Japanese versus German women [53].…”
Section: Resultsmentioning
confidence: 99%
“…Individuals with sensitive skin frequently report reddening of their skin [15,35,37,38,43,44,49,57,58]. Therefore, the assessment of erythema in skin irritation has been widely investigated, either by visual assessment [28,37,41,59,60] or by quantitative methods such as tristimulus reflectance colorimetry (a* value) [20,50,51,52], reflectance spectrophotometry (erythema index) [38,53,59] or laser Doppler flowmetry (cutaneous blood flow) [20,41,48,50,51,53,61].…”
Section: Resultsmentioning
confidence: 99%
“…Sensitive skin (SS) is a condition characterized by the perception of skin discomfort following mild stimuli, frequently without objective signs of skin irritation [13,14,15,16,17,18]. This skin condition has been shown to be highly prevalent in the Western World but, despite extensive research in the past years, no consensus on its definition and pathomechanisms has been reached [19].…”
Section: Introductionmentioning
confidence: 99%
“…Portanto, uma pele saudável tende a possuir valores de PTEA mais baixos e, portanto, uma grande quantidade de água no estrato córneo [7] . A sensibilidade desta variável é maior quando se usam testes de provocação, incluindo o teste de oclusão plástica (POST) comumente usado [8][9][10] . Este estudo tem como objetivo avaliar o impacto do uso regular de quatro semanas de duração de um gel desinfetante à base de álcool na hidratação cutânea e na função epidérmica 'barreira' in vivo, usando um modelo cinético já estabelecido de curvas de dessorção de PTEA na sequência de um teste POST.…”
Section: Introductionunclassified
“…Healthy skin tends to possess lower TEWL values and therefore, a larger amount of water in the stratum corneum [7] . The sensitivity of this variable is increased when employing provocation tests, including the commonly used plastic occlusion stress test (POST) [8][9][10] . This study aims to evaluate the impact of a four week-long regular use of an alcohol-based gel hand sanitizer on in vivo skin hydration and the epidermal 'barrier' function, using a previously established kinetic modelling of TEWL desorption curves following a POST test.…”
Section: Introductionmentioning
confidence: 99%